Comparative study of the polyphenol content-related anti-inflammatory and antioxidant activities of two Urera aurantiaca specimens from different geographical areas - Marrassini, Carla (Chin Med, 2018)
BACKGROUND: Urera aurantiaca is an Argentinean species that has been traditionally used to treat symptoms of inflammation. The aim of this study was to determine and compare the anti-inflammatory and antioxidant effects of two specimens of Urera aurantiaca obtained in the provinces of Salta and Misiones, which are two different geographical areas of Argentina. METHODS: The anti-inflammatory activity of the extracts was tested in LPS-stimulated macrophages through the DPPH radical scavenging activity, the SOD-like activity, the reducing power and the inhibition of lipid peroxidation. The anti-inflammatory activity was also evaluated by the inhibition of albumin denaturation and proteinase inhibitory action tests. The total polyphenols, flavonoids and tannins content were quantified. RESULTS: Both extracts were able to reduce the augmented NO release in LPS-activated macrophages and showed antioxidant and in vitro anti-inflammatory activities. The polyphenols content was higher in the extract obtained from the specimen from Salta than in that obtained in Misiones. This finding accounts for the higher anti-inflammatory and antioxidant properties obtained with the former. CONCLUSION: The differences in chemical composition and the biological activities observed between the extracts are probably related to the different environmental conditions found in both provinces. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13020-018-0181-1) contains supplementary material, which is available to authorized users.